Predictors of return to work after kidney transplantation: a 12-month cohort of the Japan Academic Consortium of Kidney Transplantation study. Issue 10 (3rd October 2019) - Miyake, Katsunori; Endo, Motoki; Okumi, Masayoshi; Unagami, Kohei; Kakuta, Yoichi; Furusawa, Miyuki; Shimizu, Tomokazu; Omoto, Kazuya; Shirakawa, Hiroki; Ishida, Hideki; Tanabe, Kazunari
Abstract : Objectives: To investigate the cumulative return-to-work (RTW) rate and to identify predictors of employment after kidney transplantation (KT). Design: Retrospective, outpatient-based cohort study. Setting: This was a single-centre study of the largest Japanese kidney transplant centre. Participants: We selected Japanese kidney transplant recipients aged 20–64 years who were employed in paid jobs at the time of transplantation and who visited an outpatient clinic from December 2017 to March 2018. From 797 patients, we evaluated 515 in this study. Interventions: We interviewed patients at an outpatient clinic and investigated the timing and predictors of RTW using logistic regression models. Primary and secondary outcome measures: The primary outcome was the cumulative RTW rate, and the secondary outcome was to investigate the predictors of RTW after KT. Results: Among the 515 included recipients, the cumulative overall partial/full RTW rates at 2, 4, 6 and 12 months were 22.3%, 59.0%, 77.1% and 85.0%, respectively. The median duration from transplantation to RTW was 4 months. Regarding partial/full RTW, according to the multivariable analysis including all variables, male sex was a greater predictor for RTW than female sex (OR 2.05, 95% CI 1.32 to 3.20), and a managerial position was a greater predictor than a non-managerial position (OR 2.23, 95% CI 1.42 to 3.52). Regarding full RTW, male sex (OR 1.95, 95% CI 1.25 to 3.06) and managerial position (OR 1.95, 95% CI 1.25 to 3.06) were also good predictors. Conclusions: The cumulative RTW rate was 85.0% 1-year post-transplantation. Given that cumulative RTW rates varied by sex and position, transplant and occupational physicians should support kidney transplant recipients in the aspect of returning to work. Trial registration number: UMIN000033449